Value‐iteration‐based affine nonlinear optimal control involving admissibility discussion. (25th May 2022) - Wang, Ding; Ren, Jin; Ha, Mingming
Abstract: In this article, the admissibility analysis of the value‐iteration‐based control policy is investigated for affine nonlinear dynamics. First, a series of admissible control criteria are discussed for nonlinear and linear systems. With the help of these criteria, it is more convenient to determine whether an iterative control policy is admissible or not compared with the previous work. Second, once the iterative control policy is established to be admissible by the criteria, the stability of the closed‐loop systems using the control law can be guaranteed. In addition, under certain conditions, the admissibility and asymptotic stability similar to policy iteration can be obtained. Finally, two numerical examples with the physical background are afforded to validate the effectiveness of presented theoretical results.